GOVERNMENT PENSION FUND GLOBAL: STRATEGI NORWEGIA DALAM MENGHINDARI DUTCH DISEASE - Andi Kurniawan; Arief Tri Bintang Nugraha; Nathanael Advent Christopher; Fanesya Audrei; Andi Kurniawan (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
Dutch Disease is an economic phenomenon that occurs when a commodity boom causes a currency to depreciate, reducing the competitiveness of non-resource sectors. This study analyzes Dutch Disease mitigation strategies, focusing on Norway's Government Pension Fund Global (GPFG). Using a qualitative approach and secondary data analysis, the study highlights Norway's significant capabilities. The results show that the GPFG has successfully diversified its global investments, protecting the Norwegian economy from declining oil prices and generating sustainable income. Unlike Chile, which relies on exchange rate regulation, and Saudi Arabia, which focuses on the tourism sector, Norway emphasizes long-term economic stability by investing in various sectors. The study concludes that economic diversification and prudent exchange rate management policies are key to overcoming Dutch Disease and creating economic sustainability.